A Case of Neonate with Vein of Galen Malformation Refractory to Weaning Attempts from Mechanical Ventilation Managed Successfully with Noninvasive Ventilation - Kumar, Ashutosh; Ajayan, Neeraja; Sethuraman, Manikandan; Hrishi, Ajay Prasad (Journal of Neuroanaesthesiology and Critical Care, 2018)
Weaning of patients with vein of Galen malformations (VOGM) from mechanical ventilation can be challenging in the postprocedure period due to underlying high-output cardiac failure and the fluid overload caused by the neurointervention procedure. We present the case of a neonate with VOGM who was refractory to multiple weaning attempts from mechanical ventilation and was successfully managed with noninvasive ventilation (NIV). NIV can be safely used as a method of weaning, post mechanical ventilation in this subset of patients. The use of NIV will facilitate successful weaning and reduce the incidence of extubation failure in neonates with VOGM in cardiac failure.
Keywords: vein of Galen malformations; mechanical ventilation; noninvasive ventilation